Bridging the gap between knowledge and action for health: case studies - Thamlikitkul Visanu (The World Health Organization, 2006)
Biomedical discoveries could improve people's health only if they are suited to the diverse political and social contexts, health systems and population groups. Knowledge generated through evidence-informed health policy and practice when applied to the local situation enhances the quality and efficiency of health care. This article describes four case studies on bridging the gap between knowledge and action for health in a tertiary care hospital in Bangkok, Thailand. Gaps between knowledge and action for health are classified into "know-do" and "do-know" gaps with knowledge implementation and knowledge generation being the key measures for bridging the gap.